Ananalysis Of The Effect Of Service Quality And Price Toward Consumers' Satisfaction At Agas Mart - Serly Mayang Sari; Yun Fitriano; Nia Indriasari (Penerbit Jurnal Indonesia, 2023)
Competition in the context of marketing products and services will certainly show their respective advantages. For this reason, every company must be able to realize quality that can increase customer satisfaction. This research aims to test whether there is an effect of service quality and price on consumer’s satisfaction at Agas Mart Store. In this research, the data analysis methods used were validity test, reliability test, coefficient of determination, classical assumption test, multiple linear regression test, partial test (T test) and simultaneous test (F test). And determine data collection using the questionnaire method on a sample size of 75 customer respondents who came to buy basic food ingredients at Agas Mart Store. The sampling technique uses accidental sampling (sample by chance). The results of this research show that there is a positive and significant effect between Service Quality (X1) and Price (X2) on consumer satisfaction (Y) with a value (R) obtained by an R2 (R Square) value of 0.396 or (39%) which shows that the service quality (X1) and price (X2) variables have a positive and significant influence on the consumer’s satisfaction variable (Y). Thus, the hypothesis is accepted. Based on partial testing (T test), the service quality variable has a positive and significant effect on consumer satisfaction at a significance value of less than 0.05. Meanwhile, price does not have a positive and significant effect on the consumer satisfaction variable at a significance value greater than 0.05. Based on simultaneous testing (F test) on the variables service quality (X1) and price (X2) on consumer satisfaction (Y) has a positive and significant effect because the F value is 23.598 with a significant value of 0.000 which is smaller than 0.05.